CARBON TAX ANTICIPATION, ESG DISCLOSURE, AND FINANCIAL ACCOUNTABILITY IN INDONESIA: EVIDENCE FROM IDXCARBON-LISTED ENERGY PROJECTS - ismet ismatullah; Sulthan Alif Nursyahputra (MUC Tax Research Institute, 2026)
Abstract This study examines how Indonesia’s anticipated carbon tax is reflected in environmental accounting, ESG disclosure, and audited financial reporting in high-emission state-owned energy enterprises. Using qualitative content analysis, the study triangulates sustainability reports and audited financial statements of PT PLN (Persero) and PT Pertamina (Persero) for 2022–2025 with IDXCarbon project data listed between July 2024 and April 2025. It also applies an adapted ESG risk assessment based on publicly available disclosures, focusing on carbon transition exposure and management quality. The findings show that seven IDXCarbon-listed projects generated simulated cumulative carbon tax exposure of IDR 95.49 billion, calculated using the statutory minimum rate of IDR 30,000 per ton of CO₂e. However, this exposure is not explicitly recognised as provisions or disclosed as contingent liabilities in the examined financial statements. The evidence indicates a gap between emissions disclosure, carbon market participation, and financial accountability. The study contributes project-level evidence from Indonesia’s emerging carbon market and highlights the need for clearer disclosure guidance, stronger carbon accounting, and closer alignment between ESG reporting and audited financial reporting for regulators, auditors, investors, and energy firms. Abstrak Penelitian ini mengkaji bagaimana antisipasi pajak karbon di Indonesia tercermin dalam praktik akuntansi lingkungan, pengungkapan ESG, dan pelaporan keuangan audit pada badan usaha milik negara sektor energi beremisi tinggi. Dengan analisis isi kualitatif, penelitian ini menelaah laporan keberlanjutan dan laporan keuangan audit PT PLN (Persero) dan PT Pertamina (Persero) periode 2022–2025 serta data proyek IDXCarbon yang terdaftar pada Juli 2024–April 2025. Penelitian ini juga menggunakan penilaian risiko ESG adaptif berbasis informasi publik, dengan fokus pada eksposur transisi karbon dan kualitas pengelolaan. Hasil penelitian menunjukkan bahwa tujuh proyek yang dianalisis menghasilkan simulasi eksposur kumulatif pajak karbon sebesar Rp95,49 miliar, dihitung dari tarif minimum Rp30.000 per ton CO₂e. Namun, eksposur tersebut belum secara eksplisit diakui sebagai provisi atau diungkapkan sebagai liabilitas kontinjensi dalam laporan keuangan. Temuan ini menunjukkan adanya kesenjangan antara pengungkapan emisi, partisipasi pasar karbon, dan akuntabilitas finansial. Secara empiris, studi ini memberikan bukti tingkat proyek dari pasar karbon awal Indonesia dan memperjelas batas antara pengungkapan keberlanjutan dan pengakuan akuntansi formal perusahaan. Penelitian ini menegaskan perlunya pedoman pengungkapan yang lebih jelas, penguatan akuntansi karbon, serta integrasi ESG dengan pelaporan keuangan audit.